Spatial patterns of landside trade impedance in containerized South American exports. (January 2017) - Tiller, Kara Carroll; Thill, Jean-Claude
Abstract: The paper addresses claims implicating higher domestic transportation costs as a significant barrier to Latin America's trade and economic integration - and the region's inadequate transportation infrastructure as the primary cause. The relative "trade space" for U.S.-bound containerized shipments is delineated via reverse spatial interaction modeling. Reconfiguration and reverse calibration of the doubly constrained spatial interaction model is used to derive functional distances between origins and ports of export, as a means of estimating a Trade Impedance Quotient (TIQ) for trade flows at the scale of the continent. Global and local statistics of spatial autocorrelation are then used to analyze the spatial pattern of trade impedance. With this approach, the analysis of containerized flows establishes the existence, extent, location, and spatial distribution of discrepancies in South American landside trade impedance. A large share of trade flows have trade impedance that is disproportionate to distance. Trade impedance at origins is spatially clustered for the total dataset and randomly distributed for commodity segments, and randomly distributed at destinations. Potential focus areas for high trade impedance are identified. Highlights: Delineates existence/extent/spatial distribution of landside trade impedance Estimates flow Trade Impedance Quotients; depicts clusters at origins/destinations Utilizes innovative locational verification method for containerized shipment data Relative space concept employs reverse doubly-constrained spatial interaction model. Forwards future-focused methodology for transport/various types of flow modeling